Research on the Impact of Innovative City Construction on Financial Development: Evidence from China. (23rd November 2021) - Zhao, Zhaoyang; Zheng, Yanhong; Chen, Yuhong; Ye, Chong; He, Zeyu
Abstract : Science and technology innovation is the new driving force of urban development, and it is an important vehicle to promote financial development. Innovative city attaches importance to the driving role of science and technology innovation capacity on industry development in the construction process, which will drive the development of the city's financial industry. This article takes China's innovative city pilot policy as a quasinatural experiment and uses the panel data of 235 prefecture-level cities in China from 2005 to 2017 to construct a difference-in-differences model (DID) to investigate the net effect and mechanism of the policy implementation on the financial development level of pilot cities. The results show the following: (1) the construction of innovative cities has significantly improved the financial development level of pilot cities, and the conclusion is still valid through the robustness test; (2) the financial development level promotion effect of innovative city construction has regional heterogeneity, and the financial development level promotion effect of central cities is more significant; (3) the construction of innovative cities can improve the financial development level of pilot cities by improving the intermediary effect of scientific and technological talents gathering and industrial structure upgrading.